The Role of Higher Education Integrated with Religious Moderation - Siti Marfu'ah; Anis Nurjen Nawawi (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2021)
Abstract: Higher education is a forum for the development and integration of unlimited knowledge. Various kinds of experts and researchers as well as great leaders were born from universities. It is different from increasing religious moderation through seminars or other similar things. The role of higher education institutions in shaping religious moderation through the integration of knowledge will differ from moderation through seminars. This study aims to determine the effectiveness of the role of universities in increasing religious moderation. This study uses descriptive methods and uses a qualitative approach. After conducting research, it was found that there was an increase in religious moderation in tertiary institutions through the integration of science. This shows that higher education is the right place to guide cadres who carry a modern and open ideology. Because higher education plays a role as a medium for inclusive and moderate education, religious moderation laboratory base, creator of the socio-religious environment in religion and state as well as competency builders and moderation movements. Keywords: Religious Moderation, University, moderation movements